FROM SOROGAN TO MAKNA GANDUL: ARABIC READING PEDAGOGY THROUGH KITAB KUNING IN INDONESIAN PESANTREN - Ammar Zainuddin; Hikmah Hikmah (Tunas Harapan Ummat Foundation, 2026)
Arabic reading instruction in Indonesian pesantren is characterised by pedagogical practices that support engagement with kitab kuning, including sorogan, bandongan/wetonan, nahwu-sharaf study, memorisation of grammatical matn, and vernacular glossing through makna gandul and Pegon. Previous studies have largely examined these practices separately, leaving their respective and interconnected contributions to Arabic reading competence and textual transmission insufficiently synthesised. This study examines how these practices support the reading, parsing, translation, comprehension, and interpretation of classical Arabic texts in pesantren contexts. Using a critical integrative review, it synthesises heterogeneous empirical, historical, and conceptual literature while distinguishing evidence by research design, context, and claim directness. The strongest evidence supports a recurrent pairing of sorogan and bandongan as individual verification and collective exposition, an association between nahwu-sharaf mastery and kitab-reading competence, and locally important roles for grammatical memorisation and Pegon-based glossing. Alternative grammar methods and digital supplementation show, however, that Arabic reading pedagogy in pesantren is adaptive rather than methodologically uniform. The study therefore proposes a bounded transmission-ecology model in which textual materials, grammatical resources, teacher-mediated guidance, vernacular mediation, and adaptive media interact in developing Arabic reading competence while sustaining and reconfiguring locally embedded traditions of kitab-kuning literacy. The model identifies continuity-producing functions without assuming a single national system or deliberate institutional preservation.